ANTARCTIC TARDIGRADA II. : MOLODEZHNAYA AND MT. RIISER-LARSEN AREAS (Twelfth Symposium on Polar Biology) - ウツギ, カズオ; オオヤマ, ヨシクニ; UTSUGI, Kazuo; OHYAMA, Yoshikuni (National Institute of Polar Research, 1991)
P(論文) A survey of tardigrades was attempted in two unexamined areas of Antarctica. The samples including algae or mosses were collected from 7 sites of Molodezhnaya and from 8 sites of Mt. Riiser-Larsen. Although 5 species, Echiniscus kerguelensis, Macrobiotus harmsworthi coronatus, Hypsibius arcticus, Diphascon chilenensis and Diphascon conjungens were found in both areas, 3 species; Macrobiotus montanus, Hypsibius antarcticus and Milnesium tardigradum were found only in Molodezhnaya, and another one, Isohypsibius saracenus, was found only at the foot of Mt. Riiser-Larsen. departmental bulletin paper